Analisis Framing Headline Tentang Wacana Kenaikan Harga BBM Di Harian KOMPAS dan SOLOPOS Periode Maret 2012 - Herawati, Aprillia; Serikit, Poundra Swasty Ratu Maharani (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2013)
Background of the research is author’s interest with issue of increased price of fuel oil in which it became a popular discussion among people when the issue was starting to develop. The issue of fuel oil price upsurge running about March 2012. The research uses framing analysis method by using Zhongdan Pan and Gerald M. Kosicki instruments. The headlines of Kompas and Solopos newspapers are then analyzed by using framing tool from Pan Konsicki consisting of four big structures, namely, syntax, script, thematic, and rhetoric. Findings of the research indicated that Kompas and Solopos newspaper have different frames about phenomenon of fuel oil price upsurge. The different frames used by Kompas and Solopos newspapers in framing news of the phenomenon discourse were in syntax aspect; especially those were related with headline and informant.